2018
DOI: 10.11648/j.ijse.20180201.15
|View full text |Cite
|
Sign up to set email alerts
|

Application of Support Vector Machine in Bus Travel Time Prediction

Abstract: The travel time between bus stops has obvious characteristics of time interval distribution, and the bus is a typical space-time process object, and its operation has a state transition. In order to predict the travel time between bus stations accurately, a support vector machine (SVM) algorithm is proposed based on the measured travel time between bus stations. Through a large number of GPS data in different periods of time for a reasonable classification summary bin selected the appropriate kernel function t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The study showed that the performance of the Spatio-Temporal Neural Network (STNN) (unified learning) on the dataset could reduce the mean absolute error of up to 17% for travel time prediction. Alternatively, Junyou et al [9] applied a support vector machine for predicting bus travel time to distribute many random factors such as weather, traffic congestion, and passenger flows. Moreover, Zhang Junyou et al [9] suggested that SVM can be used to analyze predictive objects and predict unknown data or new phenomena.…”
Section: Theoretical Framework Of Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The study showed that the performance of the Spatio-Temporal Neural Network (STNN) (unified learning) on the dataset could reduce the mean absolute error of up to 17% for travel time prediction. Alternatively, Junyou et al [9] applied a support vector machine for predicting bus travel time to distribute many random factors such as weather, traffic congestion, and passenger flows. Moreover, Zhang Junyou et al [9] suggested that SVM can be used to analyze predictive objects and predict unknown data or new phenomena.…”
Section: Theoretical Framework Of Related Researchmentioning
confidence: 99%
“…Alternatively, Junyou et al [9] applied a support vector machine for predicting bus travel time to distribute many random factors such as weather, traffic congestion, and passenger flows. Moreover, Zhang Junyou et al [9] suggested that SVM can be used to analyze predictive objects and predict unknown data or new phenomena. They went on to explain that the SVM has a high accuracy of learning and generalization.…”
Section: Theoretical Framework Of Related Researchmentioning
confidence: 99%
“…The TT is the result of evaluating a function based on these factors, each weighted by a regression factor. Zhang et al [11] uses a prediction method based on SVM . The data used in this proposal come from AVL systems.…”
Section: Related Workmentioning
confidence: 99%
“…For prediction of bus speed, artificial neural networks, support vector regression, Bayes networks, and mixed model are used and compared. In [13], the support vector machine is applied for the prediction of the bus travel time. The proposed method uses GPS data and is based on the prediction of the bus travel time between stations.…”
Section: Introductionmentioning
confidence: 99%